The Subject of Yashāʼ and Yaqdir in Rizq/Provision Verses - Al-Balushi, Rashid (Islamic Studies, 2023)
This article looks into some Qurʼānic verses that feature the verbs yashāʼ and yaqdir in relation to the concept of “giving rizq/provision” or “providing sustenance.” Yashāʼ means “to will”/“to wish” and yaqdir is traditionally understood to mean “to give limited provision,” but I argue that it means “to be able to.” These verses are traditionally interpreted to mean that Allah decides on whom to give abundant provision and whom to give limited provision. The article examines the linguistic structure and properties of these verses and argues that while Allah makes it possible for people to seek rizq (i.e., Allāhu yabsuṭu al-rizqa), He does not decide on whom to give abundant provision and whom to give limited provision; that is, the human being decides on the amount of rizq/provision that he/she earns. Linguistically speaking, I argue that while Allah is the subject of the verb yabsuṭ, which means “to provide in abundance” or “to make easy,” the human being is the subject of both yashāʼ and yaqdir; traditional exegesis sources analyze Allah as the subject of all three verbs. Evidence from the Qur’ān and sunnah is provided to make the case for this new understanding.